(untitled) (Journal of history, 2020)
What is the origin of the word “Kazakh” and what does it mean? Researchers differ on this point. In the article, the author focuses on the meaning of the term “Kazakh” in medieval sources and its meaning. The word “Kazakh” is also analyzed in a number of studies based on the works of foreign researchers. The Kazakh word is presented in the domestic historiography as a double word, a term born from the combination of two words, and according to foreign researchers, it is expressed in the form of a noun derived from a verb. The Kazakh word is represented in the sense of “Kazakhness”, robbery. Some German scholars have suggested that the word “Kazakh” has been used since the 15th century to refer to even the aristocracy. In this article, the author focuses on the concept of “freedom-loving, independent person” rather than the term “Kazakh” as “fugitive, homeless.” He also suggested that the term “Kazakh” should be more accurately defined as “struggle for the future, the struggle to strengthen the unity of the people” than “robbery, piracy.” Because, according to the author, almost all historical figures and historical figures who followed the path of “Kazakhness”, gradually became the founders of a new state.